2022
DOI: 10.48550/arxiv.2203.12215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physics-Driven Deep Learning for Computational Magnetic Resonance Imaging

Abstract: Physics-driven deep learning methods have emerged as a powerful tool for computational magnetic resonance imaging (MRI) problems, pushing reconstruction performance to new limits. This article provides an overview of the recent developments in incorporating physics information into learningbased MRI reconstruction. We consider inverse problems with both linear and non-linear forward models for computational MRI, and review the classical approaches for solving these. We then focus on physics-driven deep learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…As this approach leads to image-domain artifacts, carefully designed reconstruction techniques are essential to allow for clinical-quality-preserving image recovery. Recently, DL techniques have enabled state-of-the-art results in this task, enabling high acceleration and excellent reconstruction quality [ 7 , 8 , 9 , 12 , 13 , 14 , 15 , 16 , 34 , 35 , 36 , 37 , 38 , 39 ]. Their success can be attributed to the ability to learn image priors in a data-driven manner instead of the hand-crafted manner practiced in compressed sensing and dictionary learning [ 25 , 29 , 35 ].…”
Section: Mri Accelerationmentioning
confidence: 99%
See 3 more Smart Citations
“…As this approach leads to image-domain artifacts, carefully designed reconstruction techniques are essential to allow for clinical-quality-preserving image recovery. Recently, DL techniques have enabled state-of-the-art results in this task, enabling high acceleration and excellent reconstruction quality [ 7 , 8 , 9 , 12 , 13 , 14 , 15 , 16 , 34 , 35 , 36 , 37 , 38 , 39 ]. Their success can be attributed to the ability to learn image priors in a data-driven manner instead of the hand-crafted manner practiced in compressed sensing and dictionary learning [ 25 , 29 , 35 ].…”
Section: Mri Accelerationmentioning
confidence: 99%
“…Their success can be attributed to the ability to learn image priors in a data-driven manner instead of the hand-crafted manner practiced in compressed sensing and dictionary learning [ 25 , 29 , 35 ]. Furthermore, physics-guided unrolled neural networks combine the benefits of DL-based artifact-removal modules with data consistency blocks, which incorporate a physics-based model of the imaging system [ 9 ]. A large body of work has demonstrated the benefits of DL for image reconstruction in 2D MRI scans [ 7 , 8 , 9 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Mri Accelerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, these publicly available datasets are typically limited in anatomy, acquisition parameters and pathology information. Recent studies have shown that such limitations can sometimes result in hallucinations of structures or artifacts during deep learning-based MRI reconstruction [ 15 , 16 ], limiting the generalization potential of these methods and their clinical use.…”
Section: Introductionmentioning
confidence: 99%